2015
DOI: 10.1167/iovs.15-16753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Glaucoma on the Detection of Darks and Lights

Abstract: We conclude that differences in detection of darks and lights can be demonstrated over a wide range of ages, and asymmetries in dark/light detection increase with age and early stages of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 58 publications
7
38
1
Order By: Relevance
“…2A). We have previously demonstrated that humans with normal vision are faster at reporting the number of dark than light stimuli in this task (Komban et al, 2011;Zhao et al, 2015;Pons et al, 2017) and we now report the same finding for the fellow eye of amblyopic observers (Fig. 2B-D).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…2A). We have previously demonstrated that humans with normal vision are faster at reporting the number of dark than light stimuli in this task (Komban et al, 2011;Zhao et al, 2015;Pons et al, 2017) and we now report the same finding for the fellow eye of amblyopic observers (Fig. 2B-D).…”
Section: Resultssupporting
confidence: 84%
“…When performing the visual salience task, the fellow eye of amblyopic observers behaved similarly to the eye of a normal observer. As with normal (Komban et al, 2011;Zhao et al, 2015;Pons et al, 2017) or near-normal eyes (Fig. 3A-C), the fellow eyes of amblyopic observers revealed dark-light differences in visual salience more pronounced for reaction time than accuracy (Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The asymmetry itself as found in healthy subjects corroborates previously shown ON-OFF asymmetry as found for multiple visual performances (Komban et al J Vis 2013;13:ARVO E-Abstract 1022). [31][32][33][34][35][36][37][38] The fact that differences between glaucoma and healthy subjects do not clearly depend on the exact stimulus parameters (as depicted by the vertical shift of the curves in Figure 3 and the absence of clear significant interactions between glaucoma and luminance in Table 2) seems to disagree with patient experience. In a recent questionnaire study, 1 we found that glaucoma patients reported disproportionately more complaints under extreme (low, high, and changing) luminance conditions compared to controls.…”
Section: Discussionmentioning
confidence: 97%